2016
DOI: 10.5194/esurf-4-727-2016
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of sulfides and rapid weathering in recent landslides

Abstract: Abstract. Linking together the processes of rapid physical erosion and the resultant chemical dissolution of rock is a crucial step in building an overall deterministic understanding of weathering in mountain belts. Landslides, which are the most volumetrically important geomorphic process at these high rates of erosion, can generate extremely high rates of very localised weathering. To elucidate how this process works we have taken advantage of uniquely intense landsliding, resulting from Typhoon Morakot, in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
35
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 68 publications
(91 reference statements)
1
35
0
Order By: Relevance
“…These measurements of OC petro loss from soils suggest a median atmospheric CO 2 flux of 5.6 t C km −2 yr −1 to 17.1 t C km −2 yr −1 (Figure 6.S2A), consistent with previous estimates for Taiwan: (i) ≤12 t C km −2 yr −1 calculated by comparing riverine OC petro yield and TSS yield (Figure 6.S2B; , and (ii) 7 t C km −2 yr −1 to 13 t C km −2 yr −1 calculated using dissolved rhenium yield as a proxy for OC petro oxidation (Figure 6.S2B; . While similar within uncertainty, our estimates are slightly lower than catchment-specific rhenium-based values, and may suggest additional OC petro oxidation in locations not captured by our soil samples such as landslide colluvium (Emberson et al, 2016) and/or during fluvial transit (Galy et al, 2008a). This flux is on the same order of magnitude as CO 2 drawdown due to OC bio export from rivers combined with subsequent burial in marine sediments [Taiwan average: (21 ± 10) t C km −2 yr −1 ; Figure 6.S2C; Hilton et al, 2012] as well as that due to weathering of silicate minerals (LiWu River: 7.04 t C km −2 yr −1 ; Figure 6.S2D;Calmels et al, 2011).…”
mentioning
confidence: 40%
See 1 more Smart Citation
“…These measurements of OC petro loss from soils suggest a median atmospheric CO 2 flux of 5.6 t C km −2 yr −1 to 17.1 t C km −2 yr −1 (Figure 6.S2A), consistent with previous estimates for Taiwan: (i) ≤12 t C km −2 yr −1 calculated by comparing riverine OC petro yield and TSS yield (Figure 6.S2B; , and (ii) 7 t C km −2 yr −1 to 13 t C km −2 yr −1 calculated using dissolved rhenium yield as a proxy for OC petro oxidation (Figure 6.S2B; . While similar within uncertainty, our estimates are slightly lower than catchment-specific rhenium-based values, and may suggest additional OC petro oxidation in locations not captured by our soil samples such as landslide colluvium (Emberson et al, 2016) and/or during fluvial transit (Galy et al, 2008a). This flux is on the same order of magnitude as CO 2 drawdown due to OC bio export from rivers combined with subsequent burial in marine sediments [Taiwan average: (21 ± 10) t C km −2 yr −1 ; Figure 6.S2C; Hilton et al, 2012] as well as that due to weathering of silicate minerals (LiWu River: 7.04 t C km −2 yr −1 ; Figure 6.S2D;Calmels et al, 2011).…”
mentioning
confidence: 40%
“…High rates of soil erosion and landscape turnover by bedrock landslides (Hovius et al, 2000;Lin et al, 2008;Hilton et al, 2012) results in a continuous exposure of bedrock material to chemical weathering (Hilton et al, 2012;Emberson et al, 2016). The dominant lithologies are metasedimentary, decreasing in metamorphic grade from the Tananao schist on the east (peak metamorphic temperature ≈500 • C) to the Lushan sedimentary formation on the west (≤150 • C; Figure 6.S1; .…”
Section: Discussion Site Descriptionmentioning
confidence: 99%
“…Other studies have demonstrated how weathering of detrital calcite in the WSA prevents fast overall weathering there from serving as an effective drawdown for atmospheric CO 2 (Chamberlain et al, ; Jacobson et al, ). In a previous study we have shown that this is driven by weathering in landslide deposits (Emberson et al, ). In the two Taiwanese catchments we can take this further and suggest that the presence of sulfides in the bedrock combined with carbonate‐dominated weathering acts as a source for carbon dioxide rather than a sink.…”
Section: Discussionmentioning
confidence: 76%
“…For example, Jin et al () observed elevated river solute fluxes following widespread landsliding during the Wenchuan earthquake of 2008. Elevated solute fluxes were linked to recent landsliding in both the Southern Alps (Emberson, Hovius, Galy, & Marc, ) and southern Taiwan (Emberson, Hovius, Galy, & Marc, ); both studies found the effect of landslides on solute fluxes dampened on decadal timescales.…”
Section: Discussionmentioning
confidence: 99%